Engineering design of feedstock powder and relevant thermal–mechanical performance of thermal/environmental barrier coatings - Xinchang Feng; Fangwei Guo; Lirong Luo; Yuzhang Wang; Yun Long; Xiaofeng Zhao; Fei Pan; Lei Guo; Qingfeng Zeng; Jing Feng; Chunlei Wan (Journal of Advanced Ceramics)
The development of aeroengine with a high thrust-weight ratio poses great challenges for current top-coating thermal barrier coatings (TBCs) and environmental barrier coatings (EBCs) in service. Medium/high-entropy ceramics are highly promising candidate material for advanced TBCs/EBCs owing to their low thermal conductivity, high melting point, high-temperature stability, and calcium–magnesium–alumino–silicate (CMAS) resistance. Most feedstock powder used for medium/high-entropy TBCs/EBCs is prepared via traditional spray drying, which cannot fully exploit the advantages of multicomponent ceramics. The density, sphericity, inner structure, and flowability of feedstock powder affect their melting state during the thermal spraying process, which strongly affects the microstructure and properties of the deposited coatings. Therefore, the deposited coatings exhibit phase segregation, amorphous phases, and microstructure defects owing to unpredictable variations in feedstock powder with random morphologies and structures. Here, the structure and properties of feedstock powder prepared by state-of-the-art granulation technologies and their influences on the deposited coatings were systematically investigated, which can provide guidance for configuration optimization of feedstock powder and the manufacturing accuracy of the deposited coating. This review aims to bridge the gap between cutting-edge ceramics and advanced engineering technologies, thus providing concrete background knowledge and crucial guidelines for designing and developing TBCs/EBCs.